2010
DOI: 10.1177/0146167210385922
|View full text |Cite
|
Sign up to set email alerts
|

Letting People Off the Hook: When Do Good Deeds Excuse Transgressions?

Abstract: Three studies examined when and why an actor's prior good deeds make observers more willing to excuse--or license--his or her subsequent, morally dubious behavior. In a pilot study, actors' good deeds made participants more forgiving of the actors' subsequent transgressions. In Study 1, participants only licensed blatant transgressions that were in a different domain than actors' good deeds; blatant transgressions in the same domain appeared hypocritical and suppressed licensing (e.g., fighting adolescent drug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
177
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 158 publications
(191 citation statements)
references
References 19 publications
13
177
1
Order By: Relevance
“…For example, in a study examining potential discrimination directed at a lesbian, gay, bisexual person (LGB) by a heterosexual person, Krumm and Corning (2008) found that third-party observers (i.e., not targets) belonging to a perpetrator's in-group (i.e., heterosexual) were less likely to perceive the heterosexual perpetrator's behavior as discriminatory when the perpetrator had high moral credentials (e.g., activist for gay rights, affiliation with LGB) than when the perpetrator had low moral credentials. Similarly, Effron and Monin (2010) found that in ambiguous transgressions (e.g., ambiguous discriminatory behavior perpetrated by a manager against his Black employees), observers licensed the manager's prior good deeds (e.g., supported affirmative action policy) regardless of domain, compared to blatant transgressions. These studies, however, did not examine the actual target's appraisal and emotional reactions to the perpetrator's behavior directed toward the target.…”
Section: Perceived Diversity Experiences (Pde)mentioning
confidence: 98%
See 1 more Smart Citation
“…For example, in a study examining potential discrimination directed at a lesbian, gay, bisexual person (LGB) by a heterosexual person, Krumm and Corning (2008) found that third-party observers (i.e., not targets) belonging to a perpetrator's in-group (i.e., heterosexual) were less likely to perceive the heterosexual perpetrator's behavior as discriminatory when the perpetrator had high moral credentials (e.g., activist for gay rights, affiliation with LGB) than when the perpetrator had low moral credentials. Similarly, Effron and Monin (2010) found that in ambiguous transgressions (e.g., ambiguous discriminatory behavior perpetrated by a manager against his Black employees), observers licensed the manager's prior good deeds (e.g., supported affirmative action policy) regardless of domain, compared to blatant transgressions. These studies, however, did not examine the actual target's appraisal and emotional reactions to the perpetrator's behavior directed toward the target.…”
Section: Perceived Diversity Experiences (Pde)mentioning
confidence: 98%
“…Some emerging work focusing on moral transgressions and meta-perceptions suggests that minority targets may focus on cues related to whether a person behavior is perceived as due to prejudice (Effron & Monin, 2010;Krumm & Corning, 2008). This research is relevant in understanding whether PDE may matter in the experience of racial microaggressions.…”
Section: Why Experiences May Matter: Do Targets Pay Attention To the mentioning
confidence: 99%
“…If effective, moral credentials should protect actors from attributions of prejudice, and reframe their potentially incriminating actions in a more benevolent light (Effron & Monin, 2010). Although research demonstrates that people use moral credentials to license conceivably prejudiced behavior, and are personally convinced of their effectiveness (Effron, Cameron, & Monin, 2009;Merritt et al, 2012;Monin & Miller, 2001), little research has looked into how effective moral credentials actually are in shifting observers' interpretation of the behavior in question.…”
Section: Moral Credentials As Cues To Non-prejudicementioning
confidence: 99%
“…Indeed, actors who are motivated to moral credential often overestimate how credentialed observers will perceive them as being (Effron, 2014). Research also shows that transgressing in the same domain as that in which moral credentials have been established may provoke backlash from observers due to perceptions of hypocrisy (Effron & Monin, 2010). Disparaging a particular minority group from which one possesses friends may similarly be deemed hypocritical, and consequently incite more negative attributions.…”
Section: Minority Friendships As Moral Credentials?mentioning
confidence: 99%
See 1 more Smart Citation